Nikah al-Mut'ah - pleasure marriage - Dembowska, Ilona
Islam is a religion which consists of various fractions that often argue with each other about the crucial questions regulated by the Sharia law. One of them is marriage - a contract that can be permanent, but also temporary. The second form of marriage is recognized only by some Muslims. It is worth emphasizing that the Islamic perception of marriage differs from the Christian one - in Islam marriage is connected to the question of property, such a relationship is also not inseparable. Temporary marriage (in Arabic mut’ah) is recognized by Shi'ite Islam, and the Sunnis who are the majority of Muslims, treat it as heresy, because in their opinion such relationships were legal only in the times of the Prophet. The Western world perceives this kind of marriage as an example of legal prostitution with what I would like to argue. In my article, I describe the legal basis of a mut’ah derived from the Quran and the conditions which must be fulfilled. Some of them depend on the sex of spouse. A Shiite woman can marry only an equal man, hence a Muslim man. However, a man may also marry a Christian woman or a Jewish woman. He is also required to give a gift to his temporary wife, so the contract can be effective. I also write about the issue of the contract’s matter and the spouses’ declaration of will. Moreover, I describe the question of mut’ah’s duration, which is the subject of great controversy due to the fact that temporary marriage can last several hours, but also 50 years. In addition, I also write about the possibilities to dissolve mut’ah. I state the differences between mut’ah and permanent marriage. Mut’ah plays a different role (it may be described as complementary) - it is dedicated to the Muslims - Shiites, who for some reason cannot afford permanent marriage
Keywords: Islam; temporary marriage; mut’ah; Shi’ism; Shiite Islam